Anaerobic co-digestion of sludge cake from poultry slaughtering wastewater treatment and sweet potato: Energy and nutrient recovery - Damaceno, Felippe Martins; Chiarelotto, Maico; Pires Salcedo Restrepo, Juan C.; Buligon, Eduardo Luiz; Mendonca Costa, Luiz Antonio de; Lucas Junior, Jorge de [UNESP]; Silva de Mendonca Costa, Monica Sarolli (Elsevier B.V., 2019)
the energy and nutrient recovery of the sludge cake (S) from poultry slaughtering wastewater was investigated by the anaerobic co-digestion with sweet potato (P) within a wide range of S:P of 100:0 to 0:100 (mass ratio). The assay was conducted using batch anaerobic digesters (6L capacity) in laboratory scale operating at room temperature during 145 days. The highest methane yield (0.5032(3) kg VS-1 +/- 0.01) was obtained in the treatment S80P20 (68.2% CH4 +/- 0.14) indicating that co-digestion of sludge cake and sweet potato at this ratio has provided an optimum environment for microorganism activity due to the balanced nutrient content Concerning the nutrient recovery, the higher the percentage of the sludge cake in the mixture, the higher the concentration of total N and P. Multivariate analysis (Cluster and PCA) revealed that the S:P range of 100:0 to 60:40 represents the higher energetic potential recovery and the higher digestate quality with greater agronomic value without the associated phytotoxicity. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Methane specific production; Short-chain fatty acids; Digestate; Germination index